Yurisdiksi Pengadilan Agama dalam Perkara Cerai Talak antara WNI dan WNA: Studi Putusan Nomor 4816/Pdt.G/2024/Pa.Grt - Raisa Nur Alfina (Jurnal Hukum Lex Generalis, 2026)
Increasing cross-border mobility encourages the occurrence of mixed marriages between Indonesian Citizens and Foreign Citizens. However, this phenomenon finds a legal vacuum in terms of determining the jurisdiction of the Religious Court in the case of divorce if the Applicant is a foreign citizen or is abroad. This research aims to analyze the mechanism and considerations of judges in filling the legal vacancies, with Decision Number 4816/Pdt.G/2024/PA. Grt as a sample case. The research method used was in the form of normative-empirical juridical with a legislative approach and judge interviews. The results of the study show that the judge uses a teleological and systematic interpretation by making the domicile of the Respondent as the basis of jurisdiction. The novelty of this research lies in the analysis of the void of norms related to the position of the Foreigner Applicant in talaq divorce and the practice of legal discovery by the judge. Thus, this study formulates a solution in the form of strengthening concrete regulations to create legal certainty.